Eternal ganga - "Mahajan , Jagmohan" (New Delhi, 1989)
The position of the Ganga in India is unique. No other river in the world is so closely identified with a country as the Ganga is with India. Its very name evokes the panorama of Indian history- the rise and fall of great empires as well as cultural and religious movements, and the gradual growth of a number of very important cities and pilgrimage centres on its banks.
Keywords: Ganga